The interplay of dominant factors that influence adolescents’ academic performance: Motivation type and pressure vs involvement - Abildaeva, Gulnaz; Mayur, Manas; Zharnitskiy, Valeriy; Shilova, Vera (Frontiers in Education, 2022)
The study assesses the effectiveness of using motivation, pressure, and involvement in improving academic performance among adolescents on the example of Russia and Kazakhstan. The relationship between these factors and academic success was evaluated by calculating Pearson’s correlation coefficients based on the Academic Motivation Scale test’s results. The novelty of the study lies in the results: the study highlights the relationship between the individual aspects of this triad at the level of individual countries. The comparative analysis is performed using statistical data from the international knowledge assessment methodologies survey results. The findings show that intrinsic motivation and parental involvement in school life can improve adolescents’ academic performance. The negative consequences are associated with the pressure put on students by the teachers and family.